1990
DOI: 10.1017/s0016672300035217
|View full text |Cite
|
Sign up to set email alerts
|

The parental origin of de novo X-autosome translocations in females with Duchenne muscular dystrophy revealed by M27ß methylation analysis

Abstract: The parental origin of 3 de novo X-autosome translocations in females with Duchenne Muscular Dystrophy (DMD) was studied by means of methylation analysis using the X-linked probe M27 beta. In all three the translocation was found to be paternal in origin. The parental origin of X-autosome translocations in females with and without DMD is compared with other structural abnormalities of the X and with autosomal translocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 29 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In both Menkes females carrying the X-autosome translocation, and in the mother of the male patient with the intrachromosomal insertion, the structural rearrangement occurred de novo and was of paternal origin. Most of the de nuvo chromosomal rearrangements, including all the X;autoso-ma1 translocations examined so far (Bodrug et al 1990, Robinson et al 1990, Bodrug et al 1991 have been found to be of paternal origin. This finding, together with the general lack of transmission of X-autosome translocations through meiosis in the male, led Bodrug et al (1991) to suggest that the translocations causing Duchenne and Becker muscular dystrophy in females result from post-meiotic non-homologous recombination in spermiogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…In both Menkes females carrying the X-autosome translocation, and in the mother of the male patient with the intrachromosomal insertion, the structural rearrangement occurred de novo and was of paternal origin. Most of the de nuvo chromosomal rearrangements, including all the X;autoso-ma1 translocations examined so far (Bodrug et al 1990, Robinson et al 1990, Bodrug et al 1991 have been found to be of paternal origin. This finding, together with the general lack of transmission of X-autosome translocations through meiosis in the male, led Bodrug et al (1991) to suggest that the translocations causing Duchenne and Becker muscular dystrophy in females result from post-meiotic non-homologous recombination in spermiogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…The finding of paternal origin for the t(X;2) and t(X;4) translocations is of particular interest, since six other translocations in females with DMD or BMD are also of paternal origin (Bodrug et al, 1990;Robinson et al, 1990). A further four X-autosome translocations, not associated with DMD, have been studied and all are of paternal origin (Robinson et al, 1990).…”
Section: Probementioning
confidence: 99%
“…If we assume that the parent of origin of these imbalances indicates the parent in whom the translocation originated, all nine previously reported cases were paternal 7 8 10. X inactivation has also been used to study X-autosome translocations and, on the assumption that the normal X chromosome will be unilaterally inactivated, all 12 t(X;A) analysed were also shown to be paternal in origin 12. Therefore, among de novo t(X;A) and balanced translocations with breakpoint associated imbalances there is a clear paternal bias.…”
Section: Introductionmentioning
confidence: 99%